Prototipe Kontrol Lampu Dengan SCADA dan Android - Safariah, Tyas Wahyu (Journal of Energy and Electrical Engineering, 2021)
Controlling the flames lighting still using manual control, then require the officer to control the condition of the flame lights at a certain time. Therefore, the control of street lighting and the room is automatically required to facilitate the operation of the flame of the lamp. Processing using arduino Mega 2560 and NodeMCU ESP8266 as a controller, sensor DHT 11 as a detection value of the temperature and humidity sensor LDR as the control of street lighting, and the module RTC as a controller of the lighting in the room. The method used is the process of merging multiple components to form a construction. The result of the manufacture of the tool that is controlling the lights street lighting on and off based on LDR sensor, as well as the lighting on the room which is set using the set point time module RTC. the control can be operated and monitored using a SCADA system and Android, as well as can termonitoring values of temperature and humidity in a room which is displayed on the LED dot matrix. Distance control using the android system with a maximum of 22 meters.